Symbolism and Strategic Change in Academia: The Dynamics of Sensemaking and Influence - Gioia, Dennis A.; Thomas, James B.; Clark, Shawn M.; Chittipeddi, Kumar (Organization Science, 1994)
This study investigated the uses of sensemaking, influence, and symbolism in launching a strategic change effort at a university. It employed an ethnographic/interpretive approach in examining the ways that symbols, metaphors, and various subtle influence processes were used to lend meaning to concepts and possible courses of action by a task force instrumental to the strategic change process. Two distinct researcher perspectives were used: an “insider” perspective employing several informants along with an active participant-observer and an “outsider” perspective employing several researchers. Both perspectives were brought to bear as a means of countering the “researcher arrogance” that typifies organizational study by lending balanced voice to both insider and outsider interpretations of events. The findings showed that sensemaking and influence emerged as fundamental processes in the instigation of strategic change. Both processes were symbolically based and varied in directionality over the life of the task force (internally directed in the embryonic phases, and externally directed in the mature phases). Contrary to common wisdom, sensemaking and influence emerged as frequently coincident, interdependent processes that were difficult to distinguish from each other. The discovery of the common symbolic base for scnsemaking and influence also indicated that symbols served both expressive and instrumental roles: suggesting that the accepted view of symbols as predominantly expressive devices does not present a complete picture of their dynamic nature. The use of symbolism also was shown simultaneously to reveal and conceal different aspects of the change process, thus providing task force members the means to circumvent resistance while accomplishing desired action. Symbols and metaphors thus facilitated both cognitive understanding and intended action in attempting to “reinstitutionalize” a major public university via the strategic change process. Overall, the study suggests that efforts to stabilize an organizational system in flux from the systematic upheaval represented by strategic change can be understood as the symbolic interplay between sensemaking and influence.